2021
DOI: 10.1186/s12872-021-02338-2
|View full text |Cite
|
Sign up to set email alerts
|

Estimated plasma volume status (ePVS) is a predictor for acute myocardial infarction in-hospital mortality: analysis based on MIMIC-III database

Abstract: Background Estimated plasma volume status (ePVS) has been reported that associated with poor prognosis in heart failure patients. However, no researchinvestigated the association of ePVS and prognosis in patients with acute myocardial infarction (AMI). Therefore, we aimed to determine the association between ePVS and in-hospital mortality in AMI patients. Methods and results We extracted AMI patients data from MIMIC-III database. A generalized addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Our cutoff value was set at 6.52 dL/g. This is an intriguing result, as in patients with acute myocardial infarction, an ePVS ≥5.28 mL/g emerged as a risk factor for in-hospital mortality and was associated with an elevated risk of 30-day mortality ( 23 ). However, in the report by Kim et al ( 24 ), they investigated ICU patients with sepsis or septic shock.…”
Section: Discussionmentioning
confidence: 99%
“…Our cutoff value was set at 6.52 dL/g. This is an intriguing result, as in patients with acute myocardial infarction, an ePVS ≥5.28 mL/g emerged as a risk factor for in-hospital mortality and was associated with an elevated risk of 30-day mortality ( 23 ). However, in the report by Kim et al ( 24 ), they investigated ICU patients with sepsis or septic shock.…”
Section: Discussionmentioning
confidence: 99%
“…Previous researches have indicated that ePVS was a potential prognostic indicator associated with rehospitalization, and mortality in patients with AMI and HF [ 23 30 ]. Chen et al [ 24 ] reported that higher ePVS value was associated with a higher risk of in-hospital mortality in acute AMI patients. Soetjoadi et al [ 27 ] found that high ePVS was associated with in-hospital mortality in right HF.…”
Section: Discussionmentioning
confidence: 99%
“…The proposed approach had some limitations. Even though MIMIC-III is a comprehensive database and many recent research projects have been using the same database for their experiments [ 21 , 44 ], the data is almost 18 years old. Thus, we suggest that a newer multihospital database such as the Nationwide Readmission Database (NRD) [ 23 , 45 ] should be used in the future to externally validate our proposed model and its results.…”
Section: Discussionmentioning
confidence: 99%